Bias atau Realita: Analisis Wacana Konflik Timor Timur dalam Buku Teks Sejarah Indonesia Pasca Orde Baru - Azril Azifambayunasti; Annisaa Khansa Labibah; Raisha Hafandi; Athifa Raissa Putri; Linda Tiya Wati; Shendy Dyah Pramesti (Universitas Hamzanwadi, 2025)
This research aims to analyze the discourse of the East Timor conflict presented in post New Order history textbooks. It will also explore the background of its presentation. This research is departing from the facts that: first, During the 1975-1999, the Indonesian military occupied East Timor (often called integration by the Indonesian government) and was involved in a conflict related to human rights violations. Second, the conflict is part of Indonesian history that should be conveyed and become a lesson. Thus, it is necessary to explore how the curriculum and history textbooks produce and reproduce discourse related to the East Timor conflict. This research is expected to be a consideration in the process of updating the history curriculum to be more critical and open to marginalized narratives. The result show that the presentation of the East Timor conflict in post-New Order history textbooks tends to position the Indonesian government as the primary actor and ignores the complex roots of the problem. The balanced narrative is deemed unacceptable to the wider public. This is inextricably linked to the prevailing discourse that the conflict between East Timor and Indonesia was limited about the separation from the republic. However, the underlying issues involving human rights violations have never been resolved justly.